Agricultural Innovation: A Boost for Non – Oil Export Performance in Nigeria - Awele V. OHAEGBU; Omotayo A. ADEGBUYI; Ebe E. IGBINOBA (Communications of International Proceedings, 2021)
This study assesses agricultural innovation as a panacea for boosting Nigeria’s exports performance. On the basis of agro – ecosystems, conceptual, theoretical and empirical studies were reviewed. Challenges of agricultural exports on both the demand and supply side were discussed and an algorithm of production, processing, packaging and policies were derived for ensuring standard products. Analysis were mainly conceptual and factors of comparative advantage were proscribed. It was recommended that innovativeness be applied on contextual basis to achieve sustainable processes which can easily be reapplied and renewed.
Keywords: Agricultural innovation; Non-oil exports; Comparative advantage; Capacity development